Equal proportion of donor/acceptor active layer for reduced dark current in visible organic photodiode - Roslan, Suraya Annissa; Md Sabri, Amirul Ashraf; Roslan, Nur Adilah; Bawazeer, Tahani M.; Alsoufi, Mohammad S.; Aziz, Fakhra; Supangat, Azzuliani (Elsevier B.V., 2024)
The present study investigates a visible organic photodiode with low dark current of 0.002 mA/cm2. The active layer is a bulk heterojunction (BHJ) binary blended film composed of PolyN-9′-heptadecanyl-2,7-carbazole-alt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole) (PCDTBT) as a donor material along with (6,6)-Phenyl C71 butyric acid methyl ester (PC71BM) as an acceptor material. The device was fabricated using a facile spin coating technique with the structure of ITO/PEDOT:PSS/PCDTBT:PC71BM/Al. The composition of PCDTBT and PC71BM has significantly improved the absorption of the UV–visible spectrum, especially between 300 and 650 nm. The optimized device of the blended film (1:1 blend ratio) showed a good photoresponsivity of 114 mA/W, with a fast response-recovery time of 733 ms and 597 ms, respectively. It is found that the specific detectivity obtained is 1.79×109 Jones and external quantum efficiency (EQE) is 29.13 %. The results manifested the optimized device can be employed in the fabrication of a cost-effective and highly sensitive visible organic photodiode.